P13 Anti-inflammatory effects of metformin – useful in cardiovascular disease?. (26th October 2016) - Cameron, AR; Mohan, M; Forteath, Calum; McNeilly, AD; Balfour, DJK; Wong, A; Foretz, M; Lang, CC; Rena, G
Abstract : Background: Metformin is the first line drug treatment for type 2 diabetes (T2D). Along with its anti-hyperglycaemic properties, metformin is also associated with beneficial effects in cardiovascular disease (CVD). In observational studies, metformin has been associated with fewer adverse CV events. 1 How metformin induces these effects is unclear as its mechanism of action is still to be determined. Inflammation, including NF-κB signalling, has been recognised as a contributing factor to both diabetes and CVD with metformin recently reported to have effects upon inflammatory signalling. 2, 3 In this study, we have utilised primary cells and human plasma to investigate the anti-inflammatory effects of metformin and how this may be useful in CVD. Results: In mouse hepatocytes, TNFα-dependent IκB degradation and expression of pro-inflammatory mediators were inhibited by metformin and the IKKβ inhibitor BI605906. These effects upon NF-κB signalling could be separated from metabolic effects as BI605906 did not replicate metformin's actions upon lipogenic gene expression, glucose production or AMPK activation. Analysing the plasma from a non-diabetic heart failure cohort, 4 metformin use was associated with suppression of several plasma cytokines. Conclusion: This study has demonstrated that the anti-inflammatory effects of metformin are separate from its anti-hyperglycaemic actions. This knowledge indicates that metformin may be harnessed for use in 'at risk' CVD groups irrespective of diabetes status. References: Evans, et al . Diabetologia 2006;49 :930–6 Isoda, et al . Arteriosclerosis, Thrombosis, and Vascular Biology 2006;26 :611–7 Woo, et al . PLoS One 2014;9 :e91111 Wong, et al . European Journal of Heart Failure 2012;14 :1303–10